2017
DOI: 10.15583/jpchrom.2017.004
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Versatility of a Quantitative Determination Range Adjustment Technique Using In-Source CID in LC/MS/MS

Abstract: The aim of this study was to investigate the applicability of a new technique using in-source collision-induced dissociation (CID) for improving quantitative linear range of various compounds in liquid chromatography-tandem mass spectrometry (LC/MS/MS). To determine whether the linear range shift due to in-source CID occurs under various MS conditions, we investigated the quantitative linear ranges of reserpine, indomethacin, and furosemide in both electrospray ionization (ESI) and atmospheric pressure chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The plasma levels of sunitinib, N-desethyl sunitinib and axitinib were measured by modifying a previously reported method (Rodamer, Elsinghorst, Kinzig, Gutschow, We hypothesized that the nonlinearity of the calibration curve was due to saturation of the electron multiplier in the detector, and that reducing the amount of ions introduced into the mass spectrometer would be an effective solution. Utilization of in-source CID has been found to be useful for controlling the linear range of quantification in this manner (Ishii, Shimada, et al, 2016;Ishii et al, 2017). We therefore investigated the MS conditions that cause moderate in-source CID, and achieved linearity within the target range for sorafenib and pazopanib, as shown in Table 3.…”
Section: Reference Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma levels of sunitinib, N-desethyl sunitinib and axitinib were measured by modifying a previously reported method (Rodamer, Elsinghorst, Kinzig, Gutschow, We hypothesized that the nonlinearity of the calibration curve was due to saturation of the electron multiplier in the detector, and that reducing the amount of ions introduced into the mass spectrometer would be an effective solution. Utilization of in-source CID has been found to be useful for controlling the linear range of quantification in this manner (Ishii, Shimada, et al, 2016;Ishii et al, 2017). We therefore investigated the MS conditions that cause moderate in-source CID, and achieved linearity within the target range for sorafenib and pazopanib, as shown in Table 3.…”
Section: Reference Methodsmentioning
confidence: 99%
“…However, the therapeutic windows of those four TKIs are different from each other (Faivre et al, ; Fukudo et al, ; Kato et al, ; Noda et al, ; Shimada et al, ; Suttle et al, ), and it is difficult to measure their plasma concentrations under the same conditions using LC/ESI‐MS/MS. Recently, we have demonstrated the usefulness of a linear range‐shifting technique using in‐source collision‐induced dissociation (CID), and shown that this technique is capable of analyzing the concentrations of a drug and its metabolites in human plasma simultaneously (Ishii, Shimada, et al, ; Ishii, Yamaguchi, & Mano, ; Ishii et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…N2 was proposed to be MTTC because N2 and P2 had the same retention times and consistent peak area ratios (P2/N2) over the post‐administration times. The difference in the measured exact mass between N2 and P2 is probably due to in‐source CID fragmentations 11–14 …”
Section: Resultsmentioning
confidence: 99%
“…In other, the linearity ranges in MS are specified with physico-chemical properties based on the chemical structure. Recently, we proposed the application of the in-source collision induced dissociation (CID) for adjustment of MS/MS ion abundance aimed to taking advantage of LC-MS/MS [18][19][20]. This strategy shifts the linearity range to high concentration by the reduction of ion inlet via orifice probe and supports the development the simultaneous analysis methods with adjusting the linearity range by orifice voltage.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy shifts the linearity range to high concentration by the reduction of ion inlet via orifice probe and supports the development the simultaneous analysis methods with adjusting the linearity range by orifice voltage. In previous report, we adopted the strategy for the basic endogenous metabolites [18], fluoropyrimidine antineoplastic drugs [19], and the drugs such as non-steroidal anti-inflammatory drugs and diuretics [20]. In this study, we aimed to verify the strategy for major drugs used frequently in TDM practice (Fig.…”
Section: Introductionmentioning
confidence: 99%